Dorsomedial Hypothalamic Lesions Counteract Decreases in Locomotor Activity in Male Syrian Hamsters Transferred from Long to Short Day Lengths. (February 2015) - Jarjisian, Stephan G.; Butler, Matthew P.; Paul, Matthew J.; Place, Ned J.; Prendergast, Brian J.; Kriegsfeld, Lance J.; Zucker, Irving
The dorsomedial nucleus (DMN) of the hypothalamus has been implicated in seasonal control of reproduction. Syrian hamsters with DMN lesions, unlike control hamsters, do not undergo testicular regression after transfer from a long day length (14 h of light per day; LD) to a short day length (8 h of light per day; SD). SDs also markedly reduce hamster locomotor activity (LMA). To assess whether the DMN is a component of the neural circuitry that mediates seasonal variation in LMA, neurologically intact males (controls) and hamsters that had sustained lesions of the DMN (DMNx) were housed in an LD or SD photoperiod for 26 weeks. DMNx that prevented testicular regression counteracted decreases in LMA during 8 to10 weeks of SD treatment; steroid-independent effects of SDs did not override high levels of LMA in DMNx males. As in previous studies, testosterone (T) restoration increased LMA in LD but not SD castrated control males. In the present study, T also failed to increase LMA in SD-DMNx hamsters. The DMN is not necessary to maintain decreased responsiveness of locomotor activity systems to T in SDs, which presumably is mediated by other central nervous system androgen target tissues. Finally, DMNx did not interfere with the spontaneous increase in LMA exhibited by photorefractory hamsters after 26 weeks of SD treatment. We propose that DMN is an essential part of the substrate that mediates seasonal decreases in LMA as day length decreases but is not required to sustain decreased SD responsiveness to T or for development of refractoriness to SDs.